Vanilla karenchristianae (Orchidaceae): taxonomic notes and first record in the Brazilian Atlantic Forest - Barberena, Felipe Fajardo Villela Antolin; da Costa, Deivid Lucas de Lima; Borges, Ianara Tamyres Fonseca; da Costa, Messandro dos Santos Domitilo (Instituto de Ecología, A.C., 2023)
Abstract: Background and Aims: Vanilla is one of the well-known genera of the family Orchidaceae due to the ornamental, medicinal and culinary attributes of some of its taxa. The genus is pantropical and has about 120 species mostly found in the Neotropics. The objective of this study was to report the occurrence of V. karenchristianae in the Brazilian Atlantic Forest. Methods: We present a morphological description of V. karenchristianae based on the analysis of the newly found population in the state of Bahía, Brazil, and the materials collected in other sites of the country and deposited in herbaria. Also, we provide taxonomical and habitat comments, photographs, and a distribution map of V. karenchristianae in Brazil. Key results: The present record represents the most eastern distribution of V. karenchristianae and is approximately 2380 kilometers far from the nearest locality where the species has been recorded. In Brazil, V. karenchristianae is currently known from the Amazon and Atlantic Forest phytogeographic domains and from only four localities, including the one added here. Conclusions: Further recording efforts are necessary to fully understand the geographical distribution and ecological requirements of V. karenchristianae.